A captivating journey of memory and healing: A review of a novel book “Sebuah usaha melupakan” by Boy Chandra (2016) - Wajdi, Majid; Setiadewi, Ni Putu Chesya Putri; Ratih, Ni Kadek Pande Ayu; Dewi, Ni Ketut Citra; Suteja, Mutira Kristiani; Pridari, Ni Made Mira (Yayasan Mitra Persada Nusantara, 2023)
This study tries to review an Indonesian novel